Sociodemographic Factors Affecting Diabetic Dietary Behavior in People with Type 2 Diabetes Mellitus - Rondhianto, Rondhianto; Ridla, Akhmad Zainur; Hasan, Hafifah (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Dietary behavior is one of the components of self-care that is difficult for people with type 2 diabetes mellitus (T2DM) to perform. The study aimed to determine the sociodemographic factors that influence the dietary behavior of people with T2DM. The study method is an analytic observational study with a cross-sectional design. The subjects of this study were people with T2DM in Jember Regency, with a sample size was 130 respondents using a multistage random sampling technique. This study had two variables: dietary behavior as a dependent variable, measured using Self-Management Dietary Behavior Questionnaire (SMDBQ, and sociodemographic factors (age, gender, marital status, income level, education level, ethnicity, and family type) as an independent variable measured using a sociodemographic questionnaire. Data were analyzed using a multiple logistic regression test (α = 0.05). The results of the study showed that most of the respondents were 55 – 65 years old (51.5%), female (71.5%), married (85.4%), a primary education level (50.8%), low-income level (73.1%), Madurese (54.6%), and nuclear family type (37.7%). Most of the respondents had dietary behavior in the medium category (66.9%), and the sociodemographic factors that influenced diabetes diet behavior were education level (p = 0.001) and family type (p = 0.001) with R2 = 0.241. Efforts to improve self-care regarding adherence to diabetes diet behavior must pay attention to sociodemographic factors to prevent complications and improve the quality of life of people with T2DM.